Short-Term Ketogenic Diet Improves Abdominal Obesity in Overweight/Obese Chinese Young Females - Kong, Zhaowei; Sun, Shengyan; Shi, Qingde; Zhang, Haifeng; Tong, Tomas K.; Nie, Jinlei (Frontiers in Physiology, 2020)
The purpose of this study was to examine the effects of a short-term ketogenic diet (KD) on body composition and cardiorespiratory fitness (CRF) in overweight/obese Chinese females. Twenty young females (age: 21.0 ± 3.7 years, weight: 65.5 ± 7.7 kg, body mass index (BMI): 24.9 ± 2.7 kg/m2) consumed 4 weeks of normal diet as baseline, then switched to a low-carbohydrate high-fat and adequate protein KD for another 4 weeks. With the same daily caloric intake, the proportions of energy intake derived from carbohydrates, proteins and fats were changed from 44.0 ± 7.6%, 15.4 ± 3.3%, 39.6 ± 5.8% in ND to 9.2 ± 4.8%, 21.9 ± 3.4%, and 69.0 ± 5.4% in KD. The results showed that without impairing the CRF level, the 4-week KD intervention significantly reduced body weight (−2.9 kg), BMI (-1.1 kg/m2), waist circumference (-4.0 cm), hip circumference (-2.5 cm), and body fat percentage (-2.0%). Moreover, fasting leptin level was lower significantly, while serum levels of inflammatory markers (i.e., TNF-α and MCP-1) were unchanged following KD. These findings suggest that the KD can be used as a rapid and effective approach to lose weight and reduce abdominal adiposity in the overweight/obese Chinese females without exacerbating their CRF.